Penerapan Metode Analytical Hierarchy Proces Pada Penilaian Kinerja Guru TK DPK Kecamatan Garum - Erna Nur Aini (ZETROEM, 2024)
This study aims to make it easier to find out the final results of the DPK kindergarten teacher performance assessment more easily and quickly. The method used in this study uses the Analytical Hierarchy Process (AHP) method. The method used starts from communication with the teacher performance assessor. In addition, researchers also conducted research using data collection methods through interviews and gave questionnaires to definitive school principals as teacher performance assessors in Garum District. The data collected is carried out by analyzing data using the Analytical Hierarchy Process (AHP) method and using expert choice software, where each criterion, subcriteria and alternatives in the assessment by comparing one element with another, so as to provide priority value output that produces a system that provides an assessment of teacher performance. The final result of the AHP calculation PKG that obtained the highest score 0.088 or 8.8%